Molecular detection and identification of Rickettsia felis in Polygenis (Siphonaptera, Rhopalopsyllidae, Rhopalopsyllinae) associated with cricetid rodents in a rural area from central Argentina - Urdapilleta, Mara; Cicuttin, Gabriel Leonardo; de Salvo, María Nazarena; Pech May, Angélica del Rosario; Salomón, Oscar Daniel; Lareschi, Marcela (Veterinary Parasitology: Regional Studies and Reports)
Molecular methods were used to detect and identify Bartonella species in the cat fleas Ctenocephalides felis felis from Puerto Iguazú, a border area in northeastern Argentina. The fleas were collected from 12 household animals, 9 dogs (Canis lupus familiaris) and 3 cats (Felis silvestris catus) during July 2016. Out of 15C. f. felis analyzed for PCR, only one flea collected from a cat was positive (6.66%) in screened for Bartonella spp. based on the gltA gene. Bartonella clarridgeiae was identified in the genetic analyses, this specimen clustered monophyletically with others B. clarridgeiae isolated from different geographical origins (1.0 PP), even, all shared the same haplotype. The results obtained provide evidence of the presence of B. clarridgeiae in cat fleas from Argentina suggesting the probable presence of related flea-borne diseases in the region and the role of cat fleas in the transmission of Bartonella among mammals including humans. Fil: Urdapilleta, Mara. Administración Nacional de Laboratorios e Institutos de Salud "Dr. Carlos G. Malbrán". Instituto Nacional de Medicina Tropical; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Cicuttin, Gabriel Leonardo. Gobierno de la Ciudad Autónoma de Buenos Aires. Ministerio de Salud. Instituto de Zoonosis Luis Pasteur; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: de Salvo, María Nazarena. Gobierno de la Ciudad Autónoma de Buenos Aires. Ministerio de Salud. Instituto de Zoonosis Luis Pasteur; Argentina Fil: Pech May, Angélica del Rosario. Administración Nacional de Laboratorios e Institutos de Salud "Dr. Carlos G. Malbrán". Instituto Nacional de Medicina Tropical; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Salomón, Oscar Daniel. Administración Nacional de Laboratorios e Institutos de Salud "Dr. Carlos G. Malbrán". Instituto Nacional de Medicina Tropical; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; ...